X-Rated! - Danesi, Marcel. author. aut Link
XI, 180 p.
Keywords: Many attack pop culture as a crude 'sexual' and 'celebrity-based' culture that is purportedly bringing about the end of moral values. Renowned semiotician Marcel Danesi adds his signature insight to the debate by delving deep into pop culture through a consideration of symbols. Danesi's treatment of letters, such as the X in 'X-Rated,' the 'i' in 'iPod,' and other such symbols, reveals an ancient mythic structure that blends the sacred and profane dimensions of human psychic life. Danesi takes the reader on a remarkable exploration of the radical turns in American society, a society in which the search for pleasure and sexual expression often reign supreme. X-Rated! is a fascinating trip through what gives pop culture its secret appeal.